Fintech and Big Tech Credit: What Explains the Rise of Digital Lending? - Giulio Cornelli; Jon Frost; Leonardo Gambacorta; Raghavendra Rau; Robert Wardrop; Tania Ziegler (CESifo Forum, 2021)
Credit markets around the world are undergoing a deep transformation. Fintech and big tech firms are providing more lending to households and small businesses. A new database estimates that fintech credit flows reached USD 223 billion in 2019, while big tech credit reached USD 572 billion. What explains their growth? Both fintech and big tech credit are larger with higher GDP per capita (at a declining rate), higher banking sector mark-ups and less stringent banking regulation. Both are higher where economic and institutional factors favor the supply of such lending. The Covid-19 pandemic represents an important test for these new forms of credit.
Keywords: 330